PROSPEK MEGA-DEMOGRAFI MENUJU INDONESIA EMAS 2045 - Aris Ananta (Research Centre for Population, Indonesian Institute of Sciences, 2020)
The Digital revolution has gone hand in hand with the demographic revolution, featuring the future of Indonesia and the world. Everything will change unimaginably. However, this paper attempts to imagine what may happen demographically in the path toward 2045 Golden Indonesia. Triggered with the COVID-19 pandemic, this digital revolution will bring the second demographic revolution, indicating drastic changes in population mobility patterns, especially on the emergence of voluntary immobility and virtual mobility. People will go nowhere but be everywhere. The next demographic change is the trend toward de-mega-urbanisation; followed by one on fertility—on fertility below replacement level and politics of fertility; mortality-on healthy lifestyle; and family-on super-extended family, re-definition of older people, and